Increased tricarboxylic acid cycle flux in rat brain during forepaw stimulation detected with 1H[13C]NMR. - Hyder, F (1996)
NMR spectroscopy was used to test recent proposals that the additional energy required for brain activation is provided through nonoxidative glycolysis. Using localized NMR spectroscopic methods, the rate of C4-glutamate isotopic turnover from infused [1-(13)C]glucose was measured in the somatosensory cortex of rat brain both at rest and during forepaw stimulation. Analysis of the glutamate turnover data using a mathematical model of cerebral glucose metabolism showed that the tricarboxylic acid cycle flux [(V(TCA)] increased from 0.49 +/- 0.03 at rest to 1.48 +/- 0.82 micromol/g/min during stimulation (P < 0.01). The minimum fraction of C4-glutamate derived from C1-glucose was approximately 75%, and this fraction was found in both the resting and stimulated rats. Hence, the percentage increase in oxidative cerebral metabolic rate of glucose use (CMRglc) equals the percentage increases in V(TCA) and cerebral metabolic rate of oxygen consumption (CMRO2). Comparison with previous work for the same rat model, which measured total CMRglc [Ueki, M., Linn, F. & Hossman, K. A. (1988) J. Cereb. Blood Flow Metab. 8, 486-4941, indicates that oxidative CMRglc supplies the majority of energy during sustained brain activation.